Prenatal detection of terminal 9p24.3 microduplication encompassing DOCK8 gene: A variant of likely benign - Yue, Fagui (Medicine (Baltimore), 2021)
Trisomy 9p is one of the most common chromosomal partial trisomies in newborns. However, reports on prenatal 9p microduplications are rare in the clinic. This study aimed to examine the genotype–phenotype correlation and assess the clinical significance of 9p24.3 microduplication encompassing the DOCK8 gene. Eight pregnant women underwent amniocentesis for cytogenetic and genetic testing for various indications for prenatal diagnosis from January 2019 to January 2020. Chromosomal karyotypic analysis was performed on G-band metaphases that were prepared from cultured amniotic fluid cells. Chromosomal microarray analysis was carried out to detect chromosomal copy number variations. We also performed a literature review on clinical data on similar 9p24.3 microduplications to determine the genotype–phenotype correlation. We detected 123–248-kb microduplications in the region of 9p24.3 (chr9: 208454–469022), involving part of or the entire DOCK8 gene. The indications for prenatal diagnosis mainly focused on the risk of maternal serum screening for trisomy 21/18, advanced maternal age, and increased nuchal translucency. No evident structural abnormalities were observed for all fetuses, except for case 5 who presented with increased nuchal translucency in prenatal ultrasound findings. Follow-up of postnatal health was performed and showed no apparent abnormalities for cases 1 to 6 after birth. The parents of case 7 chose to terminate the pregnancy while the parents of case 8 chose to continue the pregnancy. We propose that 9p24.3 microduplications that encompass part of or the entire DOCK8 gene are variants that might be benign. However, further large-scale studies are necessary to evaluate the clinical pathogenicity. For prenatal cases with 9p24.3 microduplication, postnatal health and growth should be followed up and assessed regularly from childhood to adulthood.